A pair of blue eyes - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 2008)
"A Pair of Blue Eyes" by Thomas Hardy is a novel written during the late 19th century. This work explores themes of love and social class through the experiences of Elfride Swancourt, a young woman navigating her emotions and relationships in a rural English setting. The story is set against the backdrop of church restoration and the wild landscapes of Wessex, interweaving the intricacies of love and societal expectations. At the start of the narrative, we are introduced to Elfride, a twenty-year-old girl, who possesses a depth of emotion but lacks social sophistication. As her father, the parish vicar, is laid up with illness, Elfride prepares to host Stephen Smith, a young architect sent to oversee the restoration of a local church. The beginning paints a picture of Elfride's character$1 (Binnocent, curious, and somewhat naive$1 (Bas she contemplates the arrival of Stephen with both excitement and trepidation. Their first meeting hints at a brewing tension, setting the stage for the developing romantic intrigue amidst the constraints of their social surroundings. As Elfride grapples with her feelings in this remote part of England, Hardy begins to weave a tale that explores not just the heart, but also the complex web of class and identity in the 19th-century English society. (This is an automatically generated summary.)s
Wikipedia page on this work: https://en.wikipedia.org/wiki/A_Pair_of_Blue_Eyes
Release date is 2008-07-11
John Hamm
Keywords: Didactic fiction; Triangles (Interpersonal relations) -- Fiction; Wessex (England) -- Fiction; Separation (Psychology) -- Fiction; Elopement -- Fiction